THE AFFIRMATION OF ECOLOGICAL CAMPAIGN IN IWAN FALS ENVIRONMENT CRITICAL LYRICS - Irene Svinarky; Septriani Septriani; Hijratur Rahmi (IdeBahasa, 2023)
This study aimed to reveal the affirmation of the ecological movement through Iwan Fals' green lyrics. There are three lyrics song chosen in this study, entitled Isi Rimba tak ada tempat berpijak lagi, Tak biru lagi lautku, and Balada orang pedalaman. Actually, there are many liryca by Iwan Fals that told about the environment, but these three themes are taken as a form of musicians' rage towards the increasingly disturbed environment. Ecological Theory is the most effective approach to analyze each verse of this lyric. Garrard (2004) said that eco-critical perception helps to open, determine, explore, and even solve ecological problems in a broader and more detailed manner. The method used in this research is descriptive qualitative method, content analysis method or content analysis to examine the contents of a document. The results of this study indicate that 1) Isi Rimba tak ada tempat berpijak lagi as a representation of corrupt capitalist criticism, 2) Tak biru lagi lautku as a figurative form of ecological anxiety, and 3) Balada orang pedalaman as a romance of human life and nature which is lost by the greed of capitalist humans .